2020
DOI: 10.1186/s12939-020-01323-z
|View full text |Cite
|
Sign up to set email alerts
|

Coverage determinants of breast cancer screening in Flanders: an evaluation of the past decade

Abstract: Background Breast cancer (BC) is the most common cancer in women in the developed world. In order to find developing cancers in an early stage, BC screening is commonly used. In Flanders, screening is performed in and outside an organized breast cancer screening program (BCSP). However, the determinants of BC screening coverage for both screening strategies are yet unknown. Objective To assess the determinants of BC screening coverage in Flanders. Methods Reimbursement data were used to attribute a screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
5
3
0
Order By: Relevance
“…Also, consistently with previous evidence [18], we found that a higher percentage of people who underwent at least 2 preventive dental visits in previous 3 years was associated with higher uptake of CRC and BC screening. Considering that dental visits are not fully covered by the health insurance system in Flanders, a higher dental care may be a strong indicator of predisposition towards preventive health behaviors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, consistently with previous evidence [18], we found that a higher percentage of people who underwent at least 2 preventive dental visits in previous 3 years was associated with higher uptake of CRC and BC screening. Considering that dental visits are not fully covered by the health insurance system in Flanders, a higher dental care may be a strong indicator of predisposition towards preventive health behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…To minimize possible collider biases [16], a causal directed acyclic graph (DAG) based on prior knowledge about the Flemish organized screening programs [17], ref. [18] was employed to identify covariates for adjustment when assessing the associations between municipal characteristics and profile of BC/CRC screening uptake. A multidisciplinary brainstorming session was organized between a medical doctor, two epidemiologists (amongst whom the program manager of the Flemish CRC screening program), and a sociologist to conceptualize the exposure-outcome relationship.…”
Section: Covariates For Adjustmentmentioning
confidence: 99%
“…Consistently with a previous study [18] , we found that preventive dental care was associated with higher BC (less chances of being in Group 3 vs. Group 1) or CRC (less chances of being in Group 2 vs. Group 1) screening uptake. Considering that dental visits are not fully covered by the health insurance system in Flanders, a higher dental care may be a strong indicator of predisposition towards preventive health behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Second, with the exception of age, the other independent variables were measured for the complete municipality population and used as a proxy for the communal target population. Despite the limitations, our results substantiate previous findings at both municipal [17], [18], [24], [25], [29] and individual [26] level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation